GENERATING ENTHUSIASM TOGETHER: Networking between Pastoral Institutes in Asia - Vellguth, Klaus (Asian Horizons, 2018)
In Veritatis Gaudium Pope Francis highlights “the urgent need for ‘networking’ between those institutions worldwide that cultivate and promote ecclesiastical studies, in order to set up suitable channels of cooperation also with academic institutions in the different countries and with those inspired by different cultural and religious traditions.” One realisation of academic networking in Asia is the Network Pastoral Asia. In this Network the principals of leading pastoral institutions from all over Asia come together to support and inspire each other. During the seventh meeting of Network Pastoral Asia which took place in Myitkina (Myanmar) the principals of the institutes described their Pastoral Network as “an Asian forum of collaboration, exchange, exposure and enrichment among pastoral institutes within the universal Church, to make pastoral outreach relevant to our times.” In this article, the author refers to the different meetings of the pastoral network and explains the role of missio Aachen in initiating different networks in Asia and Africa.